Mechanotransduction use in gunshot wounds complex treatment - I. P. Khomenkо; S. V. Tertyshny; O. S. Gerasimenko (Journal of Education, Health and Sport, 2017)
New effective methods of extremities gunshot wounds treatment development has acquired a great importance because of military operations on theterritoryofDonetskand Lugansk regions ofUkraine. The development of the technological process in medical practice and personal experience allowed to develop an original approach in such patients treatment. The simultaneous use of different physical factors in extremities gunshot wounds treatment allowed us to obtain good results. The principle of mechanotransduction was used as a basis for our method: simultaneous application on the wound surface with inflammation after wound injury of debridement (primary and in some cases secondary wound surgical treatment), ultrasound (cavitation - preparation period), negative pressure (use of VAK system) and hyperbaric oxygenation. An individual algorithm of actions is developed. The efficacy of the extremities gunshot wounds treatment original method is confirmed by faster wound surface healing and the absence of complications.